2002
DOI: 10.1038/ncb902
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila HOAP protein is required for telomere capping

Abstract: HOAP (HP1/ORC-associated protein) has recently been isolated from Drosophila melanogaster embryos as part of a cytoplasmic complex that contains heterochromatin protein 1 (HP1) and the origin recognition complex subunit 2 (ORC2). Here, we show that caravaggio, a mutation in the HOAP-encoding gene, causes extensive telomere-telomere fusions in larval brain cells, indicating that HOAP is required for telomere capping. Our analyses indicate that HOAP is specifically enriched at mitotic chromosome telomeres, and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
207
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(219 citation statements)
references
References 13 publications
10
207
2
Order By: Relevance
“…These are HP2 (Shaffer et al, 2002), SU(VAR)3-7 (Delattre et al, 2000), SUUR (Makunin et al, 2002) and H3Me3K27 (Perrini et al, 2004;Ebert et al, 2004) ( Table 3). Association of HP1 and HOAP with the cap region has been demonstrated (Fanti et al, 1998;Siriaco et al, 2002;Cenci et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These are HP2 (Shaffer et al, 2002), SU(VAR)3-7 (Delattre et al, 2000), SUUR (Makunin et al, 2002) and H3Me3K27 (Perrini et al, 2004;Ebert et al, 2004) ( Table 3). Association of HP1 and HOAP with the cap region has been demonstrated (Fanti et al, 1998;Siriaco et al, 2002;Cenci et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…One candidate is HOAP, which forms a complex with HP1 (Shareef et al, 2001) and is present in cap regions of Su(var)205 null mutants (Cenci et al, 2003). A number of additional proteins appear to contribute to the stability of the HOAP/HP1 complex since, in tefu (ATM) (Oikemus et al, 2004), mre11 and rad50 mutants (Ciapponi et al, 2004), HP1 and HOAP fail to accumulate in cap regions in polytene chromosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Telomeres are heterochromatic regions. Yeast and flies with defects in activities that modify the state of chromatin also have abnormal telomere function [4][5][6] , but the putative role of chromatin-modifying activities in regulating telomeres in mammals is unknown. Here we report on telomere length and function in mice null with respect to both the histone methyltransferases (HMTases) Suv39h1 and Suv39h2 (called SUV39DN mice).…”
mentioning
confidence: 99%
“…Heterochromatic regions are enriched in methylated H3-Lys9, which creates a binding site for the chromobox proteins 9 , mediators of heterochromatin formation and epigenetic gene regulation. In D. melanogaster, HP1 is also required for telomere capping 4,5 . To investigate the impact of H3-Lys9 methylation on telomere length regulation and telomere function, we studied embryonic stem (ES) cells and mouse embryonic fibroblasts (MEFs) from SUV39DN mice 7 , which have less methylation of H3-Lys9 at the pericentric heterochromatin compared to wildtype mice 7 .…”
mentioning
confidence: 99%
“…Subsequent molecular analyses of these mutants identified genes for telomere capping proteins, including caravagio, encoding HP1/Orc-Associated Protein (HOAP). 33 At this meeting, studies of double mutant combinations involving caravagio and cell cycle checkpoint mutants were presented. These data demonstrated that telomere dysfunction activates both DNA repair and spindle checkpoint pathways.…”
Section: Multiple Functions Of Heterochromatinmentioning
confidence: 99%